Pemikiran Imam Al-Ghazali tentang Metode Mujadalah - Abdussalam, Charis (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2013)
This study aims to analyze Imam Al-Ghazali’s thought on the mujadalah method (intellectual dialogue or debate) as an approach in Islamic da’wah. The concept of mujadalah according to Al-Ghazali is rooted in the Qur’anic principle of calling to the way of Allah with wisdom, good advice, and the best form of debate, as stated in Surah An-Nahl (16:125). This research employs a qualitative approach with a descriptive-analytical method, examining Al-Ghazali’s major works such as Ihya’ Ulum al-Din, Tahafut al-Falasifah, and Al-Iqtisad fi al-I‘tiqad through Paul Ricoeur’s hermeneutic framework. The findings reveal that Al-Ghazali’s concept of mujadalah originates from a synthesis of revelation (naql), reason (‘aql), and spiritual experience (dzauq). Methodologically, mujadalah serves not merely as intellectual contestation but as a means of pursuing truth. Al-Ghazali emphasizes ethical dialogue, sincerity of intention, and moral decorum in argumentative discourse. This study concludes that Al-Ghazali’s notion of mujadalah remains highly relevant in contemporary da’wah, offering a model for rational, ethical, and spiritually grounded communication. Furthermore, it contributes to the development of Islamic communication studies by integrating rationality and spirituality within da’wah methodology.